Joyful Colors in Krishna Prakash Shah’s Abstract Artworks - Sharma , Yam Prasad (International Research Journal of MMC, 2021)
Aesthetic pleasure and joy are the dominant features of Krishna Prakash Shah's colorful compositions. Shah, one of the renowned contemporary Nepali abstract artists, presents art forms without referential and recognizable contents. In other words, the form itself is its content. The works have the power to arouse rapture and relish through harmonious colors although the viewers may not able to find fixed significance. Coherent colors, rhythmic waves, playful shapes and organic composition in his paintings contribute to create beauty and provide aesthetic pleasure to the viewers. This research paper analyzes Shah's abstract paintings from the perspective of aestheticism and traces joyful colors and rhythmic waves in his works. The study uses qualitative methods of research since there can be multiple interpretations of the same artwork, and the subjectivity of the critic has a significant role to derive the thesis statement.